2017
DOI: 10.1037/ort0000250
|View full text |Cite
|
Sign up to set email alerts
|

Mental illness disclosure decision making.

Abstract: Disclosure related to mental illness has been linked to various positive outcomes, including better mental health. However, many individuals with serious mental illness (SMI) continue to practice non-disclosure. Even though disclosure inherently occurs within the context of one's social relationships, research has generally conceptualized mental illness disclosure as an individual level phenomenon and neglected to consider preferences concerning to whom an individual discloses and the factors that influence th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 51 publications
2
29
0
2
Order By: Relevance
“…Indeed, with greater disclosure, participants were more likely to seek help from informal sources, but disclosure did not predict help-seeking from formal sources. This supports prior research that family and friends are more often recipients of disclosure than professionals for those with suicidal ideation (Husky et al 2016) and severe mental illnesses, with higher levels of disclosure associated with higher perceived social support (Pahwa et al 2017).…”
Section: Discussionsupporting
confidence: 87%
“…Indeed, with greater disclosure, participants were more likely to seek help from informal sources, but disclosure did not predict help-seeking from formal sources. This supports prior research that family and friends are more often recipients of disclosure than professionals for those with suicidal ideation (Husky et al 2016) and severe mental illnesses, with higher levels of disclosure associated with higher perceived social support (Pahwa et al 2017).…”
Section: Discussionsupporting
confidence: 87%
“…While previous research found that the visibility might have a negative impact on self‐concept of people with physical disabilities (Tam et al, ), the present study that compared two different types of disabilities (physical vs. psychiatric) indicated that the disability visibility might play a protective role for persons with physical disabilities compared to persons with psychiatric disabilities. People with visible physical disabilities who cannot hide their impairment have to actively cope with others' reactions, while people with invisible psychiatric disabilities constantly face the question of disclosure, which may negatively affect their psychological well‐being (Pachankis, ; Pahwa, Fulginiti, Brekke, & Rice, ).…”
Section: Discussionmentioning
confidence: 99%
“…Responses were reverse coded and we calculated the proportion of family members who had not been told about the attempt (i.e., nondisclosure/concealment). This approach has been similarly used in other network CSI research (Pahwa et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…An emphasis on kin networks may be of added value with attempt survivors given that family members are often the first and last line of defense in suicidal crises and tasked with more responsibilities for their relatives’ immediate welfare (i.e., maintain their loved ones’ safety) than other CSI statuses. Some network research has investigated dyadic concealment and stigma of mental illness (e.g., Pahwa, Fulginiti, Brekke, & Rice, 2017) but did not include any measures of identity. Notably, none of these studies have sought to assess all three components of a CSI, concentrated on family networks, or focused on suicide attempt survivor status.…”
Section: Literature Reviewmentioning
confidence: 99%